2001
DOI: 10.1149/1.1368097
|View full text |Cite
|
Sign up to set email alerts
|

Melt-Formable Block Copolymer Electrolytes for Lithium Rechargeable Batteries

Abstract: Microphase separated block copolymers consisting of an amorphous poly͑ethylene oxide͒ ͑PEO͒-based polymer covalently bound to a second polymer offer a highly attractive avenue to achieving both dimensional stability and high ionic conductivity in polymer electrolytes for solid-state rechargeable lithium batteries. However, due to the strong thermodynamic incompatibility typically found for most polymer pairs, the disordered, liquid state of the copolymer can rarely be achieved without the incorporation of a so… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

11
255
2
1

Year Published

2007
2007
2020
2020

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 195 publications
(274 citation statements)
references
References 29 publications
(48 reference statements)
11
255
2
1
Order By: Relevance
“…The lithium ions are complexed with EO groups [5], and together with their counterions, provide the charge carriers [6]. The nonconducting block can be tuned to confer other functions, such as mechanical robustness [3,4,6].Experimentally, the addition of lithium salts has been shown to have significant effects on the order-order and order-disorder transitions in block copolymers [3,7,8]. Among other effects, it is found that the effective parameter characterizing the immiscibility of the two blocks increases linearly with salt concentration [9,10],…”
mentioning
confidence: 99%
“…The lithium ions are complexed with EO groups [5], and together with their counterions, provide the charge carriers [6]. The nonconducting block can be tuned to confer other functions, such as mechanical robustness [3,4,6].Experimentally, the addition of lithium salts has been shown to have significant effects on the order-order and order-disorder transitions in block copolymers [3,7,8]. Among other effects, it is found that the effective parameter characterizing the immiscibility of the two blocks increases linearly with salt concentration [9,10],…”
mentioning
confidence: 99%
“…using plasticizers or using short PEO chains that have increased mobility and suppressed crystallization where the graft and branched architectures have been useful [237][238][239][240]. Also, self-assembly is used where amorphous ethylene oxide-containing domains are incorporated within block copolymeric structures, leading to synergistic properties [225,[241][242][243]. There were early efforts to combine PEO within block copolymer structures, for example by grafting short PEO grafts to the middle block of polystyrene-bpolybutadiene-b-polystyrene triblock copolymer [244,245].…”
Section: Self-assembled Ionically Conducting Polymersmentioning
confidence: 99%
“…Reducing the length of the lauryl sidechain to be only methyl, i.e. using poly(methyl methacrylate)-b-poly[oligo(oxyethylene) methacrylate], reduces the repulsion between the blocks and self-assembly does not occur [242]. However, adding CF 3 SO 3 Li leads to self-assembly and conductivity.…”
Section: Self-assembled Ionically Conducting Polymersmentioning
confidence: 99%
See 1 more Smart Citation
“…The CF 3 SO 3 -anion forms another ionic bond with the methylene group outside the helical structure when the ring structured monomers. It is suggested (Hehmeyer et al, 2007;Curtright et al, 2004;Moore and Schneider, 2001;Turcu et al, 2006;Anne-Valerie Ruzette et al, 2001;Mui et al, 2002) that ionic conduction in PEO x LiCF 3 SO 3 occurs by the cation (Li+) hopping between sites in either the single or double helix structures. Other studies showed the ionic conductivity occurs mainly in the amphorous phase rather than in the crystalline phase.…”
Section: Introductionmentioning
confidence: 99%